2011
DOI: 10.1183/09031936.00138110
|View full text |Cite
|
Sign up to set email alerts
|

COPD is associated with reduced pulmonary interstitial expression of pentraxin-3

Abstract: Pentraxin (PTX)3 is involved in antimicrobial defence, apoptotic cell clearance and extracellular matrix stability. As these processes are altered in chronic obstructive pulmonary disease (COPD), we aimed to investigate PTX3 expression in patients with this disease.PTX3 expression was quantified by immunohistochemical staining of lung tissue from neversmokers, smokers without COPD, and in patients with COPD of Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage I, II and III-IV. mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
5
11
0
Order By: Relevance
“…PTX3 has been shown to be elevated in COPD subjects compared with healthy controls in plasma34 and sputum 35. PTX3 levels have been correlated with the number of neutrophils present in sputum and have been shown to be elevated in current and ex-smokers compared with non-smokers 36. Our results support these statements.…”
Section: Discussionsupporting
confidence: 85%
“…PTX3 has been shown to be elevated in COPD subjects compared with healthy controls in plasma34 and sputum 35. PTX3 levels have been correlated with the number of neutrophils present in sputum and have been shown to be elevated in current and ex-smokers compared with non-smokers 36. Our results support these statements.…”
Section: Discussionsupporting
confidence: 85%
“…41 Patients with COPD have altered expression of other proteins involved in efferocytosis, including reduced extracellular pentraxin-3 in small airways. 43 Inhibiting efferocytosis exacerbated elastase-induced emphysema in mice. 44 …”
Section: Copdmentioning
confidence: 99%
“…There is a need for innovative prognostic markers relevant to disease progression and its complications [2]. In this report, VAN POTTELBERGE et al [1] found that lower levels of PTX3 in the lung interstitium of COPD patients were associated with airway obstruction as assessed by forced expiratory volume in 1 s (FEV1). The different levels of PTX3 were not a reflection of different amounts of PTX3 mRNA transcripts, as assessed in whole tissue extracts.…”
Section: Pentraxin-3 In Copd: Innocent Bystander or Amplifier?mentioning
confidence: 86%
“…Mantovani I n this issue of the European Respiratory Journal, VAN POTTELBERGE et al [1] report on the association between interstitial levels of the long pentraxin, PTX3, and chronic obstructive pulmonary disease (COPD). COPD remains a formidable challenge in terms of identifying prognostic markers and innovative therapeutic approaches.…”
Section: Pentraxin-3 In Copd: Innocent Bystander or Amplifier?mentioning
confidence: 99%
See 1 more Smart Citation